Mutation breeding in oil palm : a manual - Nur, Fazrin (Techniques in plantation science series, 2018)
This manual provides an introduction to mutation breeding and practical protocols on mutation induction and mutant selection in oil palm (Elaeis guineensis). Topics covered include the brief history of plant mutation breeding; health and safety considerations and guidelines in mutation induction; radio-sensitivity testing; challenges, opportunities and options for mutation breeding in oil palm; protocol for developing mutant generations for mutant selection; and services in irradiation treatments. Target audiences are students and researchers in agriculture, plant breeders, growers and end-users interested in the practicalities of producing novel oil palm genotypes for further breeding and commercial exploitation.